BACTERIOLOGICAL PROFILE AND THEIR ANTIBIOTIC SUSCEPTIBILITY PATTERN OF CASES OF CHRONIC SUPPURATIVE OTITIS MEDIA - M, Prakash; K, Lakshmi; S, Anuradha; GN, Swathi (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Chronic Suppurative Otitis Media (CSOM) is one of the common hearing problems which can cause many complications if not treated properly. Hence, the aim of the study is to identify the bacterial isolates causing CSOM and to study their antimicrobial susceptibility pattern. The study was carried out in a tertiary care hospital in Chennai from August 2012 to January 2013 for a period of six months.Â  Eighty patients of CSOM with unilateral or bilateral discharge attending the ENT Out Patient Department were included in the study. Swabs were taken and sent immediately to the microbiology laboratory and processed. Bacterial isolates were identified using standard methods and antibiotic susceptibility testing was done. Staphylococcus aureus was the most predominant organism isolated followed by Pseudomonas sp., Escherichia coli, Klebsiella sp.. The present study helped in knowing the bacteriological profile of the cases of CSOM. Empirical treatment may not be successful in all cases because of emergence of resistant organisms. Hence it is advisable to do antibiogram before starting treatment. Keywords : Chronic Suppurative Otitis Media, bacterial isolates, antibiotic susceptibility